Banks' nonperforming assets and write-offs in 1992 - Johanna Pensala; Heikki Solttila (Bank of Finland, 1993)
In this paper we present data collected by the banking supervision authorities on banks' nonperforming assets and loan losses with a view to establishing a consistent database for analysing the condition of Finnish banks and firms.
URN:NBN:fi:bof-201808011836
Keywords: 330